Case of Seoi-Nage Coaching for Elbow Joint Pain in Judo Athletes - Yamamoto, Y.; Hiraoka, H.; Sasaki, T. (Association for the Scientific Studies on Judo, Kodokan, 2021)
The aim of this study was to provide coaching guidance for seoi-nage techniques to improve performance by observing and analyzing the movements in training. Two male judo athletes who have a history of elbow joint injury were the participants in this case. The participants felt uncomfortable with Tsurite elbow when applying seoi-nage in the practice (Uchikomi and Nagekomi). The participants were unable to apply a technique under the crotch of the opponent because he had moved to the sideways opponent by the movement of Tsurite. It was probable that he tried to control the opponent by griping the collar with Tsurite when performing the technique. Therefore, the participants were instructed to practice Uchikomi in the following two points. 1) Do not put too much force on Tsurite, and place it overhead or slightly to the right, and Tsurite throws like a pitching motion. 2) In order to cultivate the feeling of catching the opponent to your back by rotating the body about 180 °from the start of the movement, make the left shoulder hit the opponent without exerting force on Tsurite to rotate your body. After the coaching, participants were able to enter the crotch to apply the seoi-nage without putting load on Tsurite and without insufficiency of the body rotation. Comparing the movements of seoi-nage before and after the instruction by motion analysis, the body was in a better pose to carry the opponent on his back without insufficient rotation when contacting with the opponent. From the above results, it was considered that understanding the pain caused by overuse or acute trauma may help to improve the habitual movement.